Evaluations of Genomic Prediction and Identification of New Loci for Resistance to Stripe Rust Disease in Wheat (Triticum aestivum L.) - Tomar, Vipin; Dhillon, Guriqbal Singh; Singh, Daljit; Singh, Ravi Prakash; Poland, Jesse; Chaudhary, Anis Ahmad; Bhati, Pradeep Kumar; Joshi, Arun Kumar; Kumar, Uttam (Frontiers in Genetics, 2021)
Stripe rust is one of the most destructive disease of wheat (Triticum aestivum L.), caused by Puccinia striiformis f. sp. tritici (Pst), and responsible for significant yield losses worldwide. Single nucleotide polymorphism (SNPs) diagnostic markers were used to identify new sources of resistance for adult plant resistance (APR) to wheat stripe rust in 141 CIMMYT advanced bread wheat lines over three years in replicated trials at Borlaug Institute for South Asia (BISA), Ludhiana. We performed a genome-wide association study and genomic prediction to aid the genetic gain by accumulating disease resistance alleles. The adult plant responses to stripe rust (YR) in 141 advanced wheat breeding lines were used to generate G x E (genotype x environment) dependent rust scores for prediction and GWAS, eliminating variation due to climate and disease pressure changes. The lowest mean prediction accuracies were 0.59 for G-BLUP and RR-BLUP, while the highest mean was 0.63 for EGBLUP and RF, using 14,563 SNPs and the G x E rust score results. RF and EGBLUP predicted ( 3%) higher accuracies compared to GBLUP and RRBLUP. Promising genomic prediction demonstrates the viability and efficacy of improving quantitative rust tolerance. The adult plant resistance (APR) to YR in these lines was attributed to eight quantitative trait loci (QTLs) using the FarmCPU algorithm. Four (Q.Yr.bisa-2A.1, Q.Yr.bisa-2D, Q.Yr.bisa-5B.2 and Q.Yr.bisa-7A) of eight QTLs linked to the diagnostic markers were mapped at unique loci (previously unidentified for Pst resistance) and possibly affirmed new loci. The statistical evidence of effectiveness and distribution of the new diagnostic markers for the resistance loci would help to develop new stripe rust resistance sources. These diagnostic markers along with previously established markers would be used to create novel DNA biosensor-based microarrays for rapid detection of the resistance loci on large panels upon functional validation of the candidate genes identified in the present study.